Influencia de la furza explosiva en la ejecución del salto y cabeceo de los jugadores de futbol de la segunda categoria del club Star de la ciudad de Riobamba, periodo agosto-octubre del2011 - Barragán Llanos, Fabricio Israel (2012)
The explosive strength is fundamental in the sporting work of the soccer as a whole, due to its anaerobic characteristics of movement, which is important to develop with the aim to improve the sporting level. The type of study used, was a non experimental descriptive cross-sectional, which permitted to identify in a more precise and clearer way the specific exercises, the training management to train the soccer players, so that they can be able to face these kind to physical demands ( explosive strength) which correspond to the competence, the explosive strength in the execution of the jump and pitch of the soccer players of the second category of the Star club of Riobamba. The objective is to determine the influence to the explosive strength in the execution of the jump and pitch of the soccer players of the second category of the Star club in Riobamba, period August- October 2011.